Pengaruh Pemanfaatan Teknologi Informasi Terhadap Pemahaman Konsep Matematis Siswa - Inayah, Nur; Nurhayadi, Nurhayadi; Rizal, Muh. (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine whether there is a significant influence between the utilization of internet information technology on the understanding of mathematical concepts of students of SMP Negeri 9 Palu City class VIII. This type of research is quantitative research. The sample in this study amounted to 60 people consisting of two classes and from 246 total population from eight classes. The sampling technique used Random Sampling. The instrument used is a questionnaire of internet information technology utilization and mathematical concept understanding test. The findings of the results of this study that there is a significant influence between the utilization of internet information technology on the understanding of mathematical concepts of students of SMP Negeri 9 Palu City class VIII where theR2 value is 0.420 or that the utilization of internet information technology contributes 42% to the understanding of students' mathematical concepts while 58% of students' understanding of mathematical concepts is influenced by other factors. The conclusion of this study is that there is a positive effect of the utilization of internet information technology on students' understanding of mathematical concepts. Keywords: Influence, Information Technology, Concept Understanding, Mathematical Ability